Expectations matter: Evaluation of brand's pro-environmental initiatives based on consumers' brand schemas and brand familiarity. Issue 1 (2nd January 2020) - Bhaduri, Gargi
ABSTRACT: This manuscript focuses on how consumers evaluate a brand's pro-environmental messages, its pro-environmental initiatives, and the brand itself as the effect of consumers' schema-congruity and their ability to resolve incongruity. The study uses brands both familiar and unfamiliar to participants. An online experiment was conducted using 402 respondents. Findings indicated that consumers' perceived message persuasiveness, their trust toward the brand's pro-environmental initiatives, brand affect, attitude toward the brand, and eventually their behavioral intention were most favorable for congruent messages, followed by when incongruity was resolved and least when incongruity was not resolved. These findings were applicable to both familiar and unfamiliar brands. In addition, consumers' attitude toward the brand before and after message exposure were different, with change being most positive for incongruity resolution for unfamiliar brands and least for incongruity nonresolution for familiar brands. The findings are important for established apparel brands that suffer from negative reputations but are willing to revitalize their images, and for new ventures who want to establish their image as pro-environmental. In addition, the findings contribute and extend theory by identifying a boundary condition for the schema-congruity theory.